(untitled) (De Musica, 2021)
When she died of cancer in June 2006, English pianist Joyce Hatto was hailed as a musical genius by the press. In the previous thirty years, despite illness, she had proven capable of mastering an incredible repertoire, encompassing nearly the entire literature ever composed for piano. Prodigy of old age, she was thought to deserve a place of honour in the annals of classical music. Which, indeed, she obtained – as a plagiarist, though. Hatto’s fake recordings, all stolen from other interpreters, have given rise to one of the greatest scandals in music history. But why do we oppose plagiarism in the first place? More than being just a matter of cultural or sentimental values, in this paper I argue that our rejection of plagiarism has to do with the idea of art itself as a special form of human accomplishment. Unrevealed forgery and plagiarism trigger our admiration through a form of deception: they disguise the accomplishment. Given the advances in the field of audio-visual material digital alteration, there might, however, be increasing confusion in the future over what counts as a fake. Is technology reshaping our view of musical authenticity?